Solvent Responsive Self‐Folding of 3D Photosensitive Graphene Architectures. (3rd December 2020) - Huang, Qi; Deng, Tao; Xu, Weinan; Yoon, ChangKyu; Qin, Zhao; Lin, Yida; Li, Tengfei; Yang, Yuqian; Shen, Michael; Thon, Susanna M.; Khurgin, Jacob B.; Gracias, David H.
Abstract : Stimuli responsive self‐folding structures with 2D layered materials (2DLMs) are important for flexible electronics, wearables, biosensors, bioelectronics, and photonics. Previously, strategies have been developed to self‐fold 2D materials to form various robots, sensors, and actuators. Still, there are limitations with scalability and a lack of design tools to obtain complex structures for reversible actuation, high integration, and reliable function. Herein, a mass‐producible strategy for creating monolayer graphene‐based reversible self‐folding structures using either gradient or differentially cross‐linked films of a negative epoxy photoresist widely used in microfluidics and micromechanical systems, namely, SU8 is demonstrated. Wafer‐scale patterning and integration of complex and functional devices in the form of rings, polyhedra, flowers, and bidirectionally folded origami birds are achieved. Also, gold (Au) electrodes to realize functional graphene–Au Schottky interfaces with enhanced photoresponse and 3D angle sensitive detection are integrated. The experiments are guided and rationalized by theoretical methods including coarse‐grained models, specifically developed for the tunable mechanics of this photoresist that simulate the folding dynamics, and finite element method (FEM) electromagnetic simulations. This work suggests a comprehensive framework for the rational design and scalable fabrication of complex 3D self‐actuating optical and electronic devices through the folding of 2D monolayer graphene. Abstract : Three‐dimensional integrated and photoresponsive microstructures composed of high‐quality monolayer or few layer graphene are assembled in a range of shapes using differentially photocross‐linked SU8. Experiments are rationalized by simulations and highlight a general approach for creating chemically responsive and reversible functional hybrid structures of relevance to biosensing, bioelectronics, wearables, and soft robotics.